A VLP-based vaccine targeting ANGPTL3 lowers plasma triglycerides in mice. Issue 40 (24th September 2021) - Fowler, Alexandra; Sampson, Maureen; Remaley, Alan T.; Chackerian, Bryce
Highlights: ANGPTL3 and ANGPTL4 are mediators of lipoprotein metabolism that inhibit lipoprotein lipase (LPL) activity. Vaccination using virus-like particles (VLPs) targeting ANGPTL3 and ANGPTL4 elicits high-titer IgG antibody responses. Immunization with ANGPTL3 VLPs lowers steady-state plasma triglycerides and enhances LPL activity. Abstract: Elevated triglycerides (TGs) are an important risk factor for the development of coronary heart disease (CHD) and in acute pancreatitis. Angiopoietin-like proteins 3 (ANGPTL3) and 4 (ANGPTL4) are critical regulators of TG metabolism that function by inhibiting the activity of lipoprotein lipase (LPL), which is responsible for hydrolyzing triglycerides in lipoproteins into free fatty acids. Interestingly, individuals with loss-of-function mutations in ANGPTL3 and ANGPTL4 have low plasma TG levels, have a reduced risk of CHD, and are otherwise healthy. Consequently, interventions targeting ANGPTL3 and ANGPTL4 have emerged as promising new approaches for reducing elevated TGs. Here, we developed virus-like particle (VLP) based vaccines that target the LPL binding domains of ANGPTL3 and ANGPTL4. ANGPTL3 VLPs and ANGPTL4 VLPs are highly immunogenic in mice and vaccination with ANGPTL3 VLPs, but not ANGPTL4 VLPs, was associated with reduced steady state levels of TGs. Immunization with ANGPTL3 VLPs rapidly cleared circulating TG levels following an oil gavage challenge and enhanced plasma LPL activity. These data indicate that targeting ANGPTL3 by active vaccination is a potential alternative to other ANGPTL3-inhibiting therapies.